Biomimetic and Bioinspired Membranes for New Frontiers in Sustainable Water Treatment Technology - Abdelrasoul, Amira; Doan, Huu; Lohi, Ali (IntechOpen, 2017)
Biomimetic and bioinspired membranes are the most promising type of membrane for multiple usage scenarios, including commercial separation applications as well as water and wastewater treatment technologies. In recent years, aquaporin biomimetic membranes (ABMs) for water purification have raised considerable interest. These membranes display uniquely favorable properties and outstanding performances, such as diverse interactions, varied selective transport mechanisms, superior stability, high resistance to membrane fouling, and distinct adaptability. Biomimetic membranes would make a significant contribution to alleviate water stress, environmental threats, and energy consumption.